DEVELOPING READING MATERIAL BASED-ON LOCAL CULTURE FOR JUNIOR HIGH SCHOOL IN KABUPATEN REJANG LEBONG - Leni Agustina; Alamsyah Harahap (Universitas Bengkulu, 2018)
Nowadays, the developing and appreciating material based on student’s local culture is very attractive. The objectives of this research are to know the existing folktales in students’ book, to identify local folktales that suitable to be included in the English students’ book and to know how to include the local folktales in the English students’ book for ninth grade of Junior High School in Rejang Lebong. This research adapted the R&D model proposed by Borg and Gall (1983) with some modifications. The data was taken from students and teachers of SMP Negeri 1 Rejang Lebong, SMP Negeri 2 Rejang Lebong and SMP Negeri 5 Rejang Lebong through questionnaire and interview. The first result of this research shows that students like the existing folktales in students’ book but sometimes they found difficulties in comprehending it. The second result identifies three siutable local folktales suitable to be included in the students’ book; Legenda Batu Menangis (62.4%), Lalan Belek (66.7%) and Muning Raib (66.7%). The third result shows that the developed material can be used as supplementary reading material. In conclusion, the existing folktales in the student’s book are good but not contextual, there are highly three suitable local folktales to be included in students’ book (Legenda Batu Menangis, Lalan Belek, and Muning Raib) and the way to include the suitable local folktales in English students’ book is as supplementary reading material. As suggestion, the next researcher can conduct further study on evaluation by using try out of this material development.